Performance on the Operant Test Battery in young children exposed to procedures requiring general anaesthesia: the MASK study - Warner, David O.; Chelonis, John J.; Paule, Merle G.; Frank, Ryan D.; Lee, Minji; Zaccariello, Michael J.; Katusic, Slavica K.; Schroeder, Darrell R.; Hanson, Andrew C.; Schulte, Phillip J.; Wilder, Robert T.; Sprung, Juraj; et al. (British journal of anaesthesia : BJA, 2019)
It is not known whether the neurotoxicity produced by anaesthetics administered to young animals can also occur in children. Exposure of infant macaques to ketamine impairs performance in selected domains of the Operant Test Battery (OTB), which can also be administered to children. This study determined whether a similar pattern of results on the OTB is found in children exposed to procedures requiring general anaesthesia before age 3 yr. We analysed data from the Mayo Anesthesia Safety in Kids (MASK) study, in which unexposed, singly-exposed, and multiply-exposed children born in Olmsted County, MN, USA, from 1994 to 2007 were sampled using a propensity-guided approach and prospectively underwent OTB testing at ages 8–12 or 15–20 yr, using five tasks that generated 15 OTB test scores. In primary analysis, none of the OTB test scores depended upon anaesthesia exposure status when corrected for multiple comparisons. Cluster analysis identified four clusters of subjects, with cluster membership determined by relative performance on the OTB tasks. There was no evidence of association between exposure status and cluster membership. Exploratory factor analysis showed that the OTB scores loaded onto four factors. The score for one factor was significantly less in multiply-exposed children (mean standardised difference –0.28 [95% confidence interval, –0.55 to –0.01; P=0.04]), but significance did not survive a sensitivity analysis accounting for outlying values. These findings provide little evidence to support the hypothesis that children exposed to procedures requiring anaesthesia show deficits on OTB tasks that are similar to those observed in non-human primates.